2013
DOI: 10.1128/aem.01728-13
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Emerging Shiga Toxin-Producing Escherichia coli O26:H11/H Sequence Type 29 (ST29) Clone in Human Patients and Healthy Cattle in Switzerland

Abstract: Shiga toxin-producing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 16 publications
6
38
0
Order By: Relevance
“…We confirmed that the new highly pathogenic EHEC O26:H11 clone ST29 is circulating in France and constituted most of the stx 2 -harboring EHEC O26:H11 strains studied here, as 16 of the 23 strains appeared to correspond to this clone (ST29). This finding confirms observations made by others in different countries (3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, the characteristics of many of the strains analyzed here differed somewhat from the characteristics described previously.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…We confirmed that the new highly pathogenic EHEC O26:H11 clone ST29 is circulating in France and constituted most of the stx 2 -harboring EHEC O26:H11 strains studied here, as 16 of the 23 strains appeared to correspond to this clone (ST29). This finding confirms observations made by others in different countries (3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, the characteristics of many of the strains analyzed here differed somewhat from the characteristics described previously.…”
Section: Discussionsupporting
confidence: 73%
“…This dominant profile (52% of the strains) was reported previously with a much lower prevalence (8)(9)(10). The possibility that the plasmid was lost during culture of the strains could not be excluded, however.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations